Найдите значение выражения: [latex] \frac{(8^{n+1} + 8^{n})^{2} }{(4^{n} - 4^{n-1})^{3} }, n [/latex] ∈ N Вычислите: [latex] \frac{6^{6} * 2^{3} - 3^{6} }{6^{6} + 3^{3} * 6^{3} + 3^{6} } [/latex]
Найдите значение выражения:
[latex] \frac{(8^{n+1} + 8^{n})^{2} }{(4^{n} - 4^{n-1})^{3} }, n [/latex] ∈ N
Вычислите:
[latex] \frac{6^{6} * 2^{3} - 3^{6} }{6^{6} + 3^{3} * 6^{3} + 3^{6} } [/latex]
Ответ(ы) на вопрос:
[latex]1)8 ^{2n} *(8+1)^2/4 ^{3n-3} *(4-1)^3=2 ^{6n} *81/2 ^{6n-6} *27=2^6*3=64*3[/latex][latex]=192[/latex]
[latex]2)3^6(2^6*2^3-1)/3^6(2^6+2^3+1)=(512-1)/(64+8+1)=511/73=[/latex][latex]7[/latex]
Не нашли ответ?
Похожие вопросы